Drone-based herbicide application for energy saving, higher weed control and economics in direct-seeded rice (Oryza sativa) - PAUL, R AROCKIA INFANT; ARTHANARI, P MURALI; PAZHANIVELAN, S; KAVITHA, R; DJANAGUIRAMAN, M (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted at Tamil Nadu Agricultural University, Coimbatore during kharif (rainy) and rabi (winter) seasons of 2022 and 2023 to evaluate the efficiency, energy and economics of drone-based herbicide application in direct-seeded rice (Oryza sativa L.). The study was carried out with application of pre-emergence, early post-emergence and post-emergence herbicides using drone and knapsack sprayer to assess the weed control efficiency. Treatments included pretilachlor followed by (fb) application of post-emergence herbicides, such as bispyribacsodium (Na), fenoxyprop ethyl + carfentrazone ethyl and early post-emergence herbicides, such as bispyribac-Na, fenoxyprop ethyl + carfentrazone ethyl, bispyribac-Na fb post-emergence of fenoxyprop ethyl + carfentrazone ethyl, weed-free check and unweeded check. Application of pretilachlor fb bispyribac-Na using knapsack sprayer reduced weed density from 83 to 87% and weed dry weight from 81 to 83% over unweeded plot. Moreover, it was found on par with drone application of same herbicides in both seasons. Pretilachlor fb bispyribac-Na application through knapsack sprayer and drone produced higher grain yield and it was comparable with weed-free plot. Higher net return, benefit: cost ratio (2.27 and 2.09), energy-use efficiency (10.86 and 9.55 MJ) and energy productivity (0.81 and 0.71 kg/MJ) were noticed with drone application of pretilachlor fb bispyribac-Na in both the seasons. From the experiment, drone application of pretilachlor fb bispyribac-Na is found as an effective strategy to manage weeds in direct-seeded rice and more advantageous in terms of energy-use and profitability.